The Role of Porter's Strategy as a Mediating Variable Between Business Strategy Planning and Performance in MSMEs - Fatchuroji, Acep; Wahyudhi, Candra Agus; -, Damayanti; Oktariani, Mutiya (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of business strategy planning on the performance of MSMEs in Merauke Regency and to test the mediating role of Porter's generic strategies, which include cost leadership, differentiation, and focus strategy. A quantitative approach was used using Partial Least Squares analysis techniques on 139 MSME respondents from four industrial sectors. The results indicate that business strategy planning has a positive effect on MSME performance, both directly and indirectly through three competitive strategies. Each strategy proved to be a significant mediator in the relationship between planning and performance. These findings emphasize the importance of documented business planning as a foundation for implementing competitive strategies to achieve optimal performance. This study contributes to the development of competitive strategy models in the context of MSMEs and provides practical implications for business actors and local policymakers